2005
DOI: 10.1017/s1461145705005997
|View full text |Cite
|
Sign up to set email alerts
|

Transmission disequilibrium of polymorphic variants in the tryptophan hydroxylase-2 gene in children and adolescents with obsessive–compulsive disorder

Abstract: Dysfunction of the central serotonergic system has been implicated in the pathophysiology of obsessive-compulsive disorder (OCD). The genetic contribution to the development of OCD is particularly high in early-onset OCD. The aim of this study was to investigate the effect of polymorphic variants in the gene of the novel brain-specific tryptophan hydroxylase-2 (TPH2), the rate-limiting enzyme of serotonin (5-HT) synthesis in the brain, in OCD with disease onset in childhood and adolescence. We analysed two com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
62
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 29 publications
1
62
0
1
Order By: Relevance
“…23 Since the discovery of the TPH2 gene in 2003, 4 14 published studies have examined possible associations between TPH2 SNPs and various mental disorders including major depression, 17,24,25 bipolar disorder, 26 anxiety disorders, 27,28 attention-deficit/ hyperactivity disorder (ADHD), 29,30 autism 31 or suicidal behavior. 17,[32][33][34][35][36] The results of these studies have been mixed, with nine studies showing weak, but statistically significant associations between one or more TPH2 SNP and a specific mental disorder, 17,[24][25][26][27][29][30][31][32] and five showing no significant associations. 28,[33][34][35][36] Most of the studies reporting negative results failed to detect statistically significant associations for SNPs in the putative promoter region or intronic SNPs in the 5 0 -end of the gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Since the discovery of the TPH2 gene in 2003, 4 14 published studies have examined possible associations between TPH2 SNPs and various mental disorders including major depression, 17,24,25 bipolar disorder, 26 anxiety disorders, 27,28 attention-deficit/ hyperactivity disorder (ADHD), 29,30 autism 31 or suicidal behavior. 17,[32][33][34][35][36] The results of these studies have been mixed, with nine studies showing weak, but statistically significant associations between one or more TPH2 SNP and a specific mental disorder, 17,[24][25][26][27][29][30][31][32] and five showing no significant associations. 28,[33][34][35][36] Most of the studies reporting negative results failed to detect statistically significant associations for SNPs in the putative promoter region or intronic SNPs in the 5 0 -end of the gene.…”
Section: Discussionmentioning
confidence: 99%
“…Mossner et al 27 described an association between obsessive-compulsive disorder (OCD) and the G-C haplotype for rs4570625 and rs4565946, SNPs located in the putative regulatory region and intron 2, respectively. Walitza et al 29 described a weak association between regulatory region SNPs (rs4570625 and rs11178997) and attention-deficit hyperactivity disorder (ADHD).…”
Section: Discussionmentioning
confidence: 99%
“…5,6 TPH1 mRNA is expressed in the CNS at extremely low levels, 7 although TPH1 mRNA is robustly expressed in the pineal gland, where TPH mediates melatonin biosynthesis. 5,8 Recent data have suggested a possible association between TPH2 polymorphisms and a variety of psychiatric disorders including major depression, 9-14 suicide, 13,14 attentiondeficit/hyperactivity disorder, [15][16][17] autism, 18 bipolar disorder, 19 and obsessive compulsive disorder. 16 In addition, it has recently been shown that polymorphisms in the 3 0 -UTR of rhesus monkey TPH2 modulate hypothalamic-pituitary-adrenal (HPA) axis function presumably through changes in TPH2 expression.…”
Section: Introductionmentioning
confidence: 99%
“…5,8 Recent data have suggested a possible association between TPH2 polymorphisms and a variety of psychiatric disorders including major depression, 9-14 suicide, 13,14 attentiondeficit/hyperactivity disorder, [15][16][17] autism, 18 bipolar disorder, 19 and obsessive compulsive disorder. 16 In addition, it has recently been shown that polymorphisms in the 3 0 -UTR of rhesus monkey TPH2 modulate hypothalamic-pituitary-adrenal (HPA) axis function presumably through changes in TPH2 expression. 20 These data suggest that changes in the expression and/or function of TPH2 may be associated with psychiatric disease and emphasize the need to understand what makes TPH isoforms distinct with regard to function and regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Variants in the TPH2 sequence have been associated with a spectrum of psychiatric diagnoses, such as obsessive compulsive disorder, affective disorders and attention-deficit/hyperactivity disorder (ADHD). [1][2][3][4][5][6] It has been proposed that naturally occurring variants of TPH2 with decreased enzyme activity could cause deficiency of serotonin production and an increased risk of developing affective disorders. 3 However, all the TPH2 variants described so far are either situated in non-coding regions or are missense mutations with significant residual activity.…”
mentioning
confidence: 99%